Prevalence of Para-Pneumonic Effusion and the Associated Factors among Children: A 3-Year Experience in a Single Tertiary Hospital - Alanazi, Yousef; Alkhurayji, Abdullatif; Alawni, Omar; Alkhalaf, Hamad (International Journal of Child Health and Nutrition, 2024)
Background: Previous studies have highlighted the significant morbidity associated with para-pneumonic effusions in pediatric populations. However, comprehensive data on the prevalence and associated factors in children remain limited, particularly in tertiary care settings. Methods: A retrospective cohort study was conducted over a three-year period at a single tertiary hospital. Medical records of pediatric patients diagnosed with pneumonia were reviewed to identify cases of para-pneumonic effusion. The study analyzed demographic data, clinical presentations, laboratory findings, and management approaches to determine factors associated with the development of para-pneumonic effusions. Results: 150 patients were identified with para-pneumonic effusions. The majority of patients with effusions were male (60%) and under five years of age (70%). Factors significantly associated with the development of effusions included the presence of comorbidities (p<0.01), higher CRP levels (p<0.05), and hospital-acquired pneumonia (p<0.001). The length of hospital stay was notably longer in patients with effusions than those without (p<0.001). Conclusion: The study found a considerable prevalence of para-pneumonic effusions among children with pneumonia in a tertiary hospital setting. Notably, associated factors were underlying comorbidities, elevated inflammatory markers, and hospital-acquired infections. These findings underscore the need for heightened surveillance and tailored management strategies in high-risk pediatric populations to mitigate the impact of effusions.